Evaluation of 93 accessions of African yam bean (Sphenostylis stenocarpa) grown in Ethiopia for physical, nutritional, antinutritional, and cooking properties - Shitta, N.S.; Abebe, A.T.; Oselebe, H.O.; Edemodu, A.; Alamu, Emmanuel Oladeji; Abberton, Michael T.; Maziya-Dixon, Busie; Adesokan, Michael; Fenta, B.; Abtew, W.G. (Hindawi Limited, 2022)
African yam bean has immense food and nutrition potential and is resilient to adverse environmental conditions. Despite its potential, the crop is underutilized, which could be attributed to seed hardness (requiring about 6–24 hours of cooking time); and the abundance of antinutrient factors (tannin, phytate, and oxalate). This study evaluated the physical (seed hardness, cooking time) and chemical compositions (crude protein, tannin, phytate, and oxalate) of 93 AYB accessions grown in Ethiopia. The seed hardness of each accession was determined by the compression force and compression time using Texture Analyzer, whereas cooking time was ascertained using Mattson Bean Cooker. The accession’s crude protein level, tannin, oxalate, and phytate were investigated from flour samples using standard laboratory procedures. Highly significant () differences were observed for cluster means of compression force, cooking time, and oxalate. The accessions were grouped into three clusters: cluster-II was prominent with 42 accessions, while cluster-I had the least (25). The mean values for compression force ranged from 50.05 N ± 10.25 (TSs-423) to 278.05 N ± 13.42 (TSs-378) whereas compression time varied from 0.35 secs ± 0.02 (TSs-334) to 5.57 secs ± 6.12 (TSs-62B). Cooking time ranged from 127.50 mins ± 2.12 (TSs-82A) to 199.50 mins ± 10.61 (TSs-138B); crude protein ranged from 15.41% ± 0.11 (TSs-269) to 24.51% ± 0.22 (TSs-446). Tannin ranged from 0.61 mg/g ± 0.02 (TSs-47) to 9.62 mg/g ± 0.03 (TSs-334) likewise, phytate ranged from 0.28 ± 0.01 (TSs-137) to 7.01 ± 0.10 (TSs-3). Accessions TSs-55; TSs-82 showed the lowest oxalate content of 0.21% ± 0.01; 0.21% ± 0.00, respectively. Similarly, TSs-352; TSs-47 revealed the most abundant tannin content of 0.70 ± 0.00 and 0.70 ± 0.07. The correlation analysis revealed a low positive and significant () association (r = 0.24) between protein and phytate content.